A Review on the Application of PD-1 Blockade in EBV-Associated Nasopharyngeal Carcinoma Immunotherapy - Jin Bian; Yan Niu; Yanli Ma; Fuhua Chen; Ning Ma (Applied Bionics and Biomechanics)
Epstein-Barr virus (EBV) linked with nasopharyngeal carcinoma (NPC) is considered to be one of the most prevalent head and neck malignancies in East and Southeast Asia. Although radiotherapy and chemotherapy are effective treatments for NPC, they have immunosuppressive effects. Immunotherapy has got considerable attention of clinicians for cancer treatment in recent years due to proven success of PD-1/PD-L 1 inhibition in solid tumors trials. The distinct immunological environment of EBV-associated NPC presents a reasonable therapeutic target for PD-1/PD-L 1 inhibition. Immune checkpoint blockade therapy targeting the programmed cell death-1 (PD-1) and programmed cell death ligand-1 (PD-L 1) receptors have shown efficacy in early phase I clinical trials, with ongoing phase III clinical trials. Herein, we have extensively addressed the role of the PD-1/PD-L1 axis in the immunotherapy of EBV-associated NPC. Immunotherapeutic strategies are anticipated to enter mainstream clinical practise and provide long-term remissions in patients with severe NPC.